The Influence of Science Subject Spesific Pedagogy (SSP) of Lab Work-Based toward Science Process Skills of Students at SMPN 2 Tolitoli - Elyas Djufri; Insih Wilujeng (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2017)
This research aims to find out the influence of Science Process Skills between a group of students who learn Science by using subject spesific pedagogy (SSP) of the elaborative lab work result - based with the ones who learn by using subject spesific pedagogy (SSP) of conventional lab work - based in the IX grade of SMPN 2 Tolitoli in academic year 2016/2017. The type of research is quasi-experimental study using non equivalent control group design. Two classes are chosen as samples by using random sampling techniques, they are class IXB as the experimental class and IXC as the control class. Each class consists of 31 Students. The data of science process skills (SPS) are obtained through observation sheets. Then the data are analyzed by descriptive analysis techniques on significance of 5%. The result shows the significance is 0,005, thus it can be concluded that the application of SSP during teaching and learning process of Science of the elaborative lab work result-based significantly effects on science process skills (SPS) of the students compared with the conventional ones. It is also reinforced by the improvement of criteria of SPS, which is 0,5 (medium category) for the experimental class and 0,1 (low category) for the control class.